Fairground Architecture and Crowds. Issue 2 (4th May 2019) - Walker, Stephen
ABSTRACTS: Drawing on fieldwork at travelling fairs in England, this article uses a number of concepts—crowd crystals, involvement contours, cacophony, intercalary elements—to read the heterogeneous interrelationships between fair-going crowd dynamics and fairground architecture. The article notes an apparent lack of interest in both these entities (from crowd theory and architectural theory, respectively); establishing an historiographical account of this (lack of) interest, it situates fairground crowds within and against crowd behaviour, and crowd theory more generally, and draws on assemblage theory to develop an account of the fair-going crowd, and fairground architecture, that is responsive to its particular characteristics.